1972
DOI: 10.1103/physrevlett.29.307
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Anomaly in the Excitation Function of the ReactionH2(p,γ)3

Abstract: The excitation function of the capture reaction 2 U(p, y) 3 He has been measured in the range 1^ = 10-17.5 MeV. An anomaly was observed and is interpreted as a broad resonance in 3 He at an excitation energy of 14.5 ±0.5 MeV with a width of about 2 MeV.The study of possible excited states in the three-nucleon system was initiated both experimentally and theoretically when Ajdacic et al. 1 reported evidence for the existence of a bound trineutron in the reaction 3 H(w, p)nnn. In the inelastic reaction 3 He(/>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…1 we show our theoretical results for the total cross section of 3 He photodisintegration compared to most of the available experimental data [2][3][4][8][9][10][11][12][13] up to E γ = 40 MeV. Not shown are the data by van der Woude et al [15] and Chang et al [17] who found evidence for an excited state in their measurements. This resonance behavior has never been confirmed by any other group.…”
Section: Resultsmentioning
confidence: 64%
“…1 we show our theoretical results for the total cross section of 3 He photodisintegration compared to most of the available experimental data [2][3][4][8][9][10][11][12][13] up to E γ = 40 MeV. Not shown are the data by van der Woude et al [15] and Chang et al [17] who found evidence for an excited state in their measurements. This resonance behavior has never been confirmed by any other group.…”
Section: Resultsmentioning
confidence: 64%